Triple A & P Sdn Bhd: Laundry service / Muhammad Aiman Zahid Zulkifli ...[et al.] - Zulkifli, Muhammad Aiman Zahid; Khairulfaizal, Adam Afiq; Aminudin, Muhammad Aniq Iqmal; Zainal, Mohamad Syafie (2023)
Triple A & P is a new limited liability company that will be founded in Kota Masai, Pasir Gudang, Johor. The firm will offer four services: dry cleaning, wash and fold, curtain cleaning, and ironing. The business provided frequent residential pick-up and delivery services. Triple A & P is a full-service laundry committed to constantly offering great customer satisfaction by providing dependable machines and a clean, pleasurable environment at a competitive price and value connection. The time is ideal for launching this new enterprise. After two months of hunting for the ideal spot, one was eventually identified. The need for washing services, the owner's dreams to one day establish his own laundry business, and the skills to support the enterprise all combined to make it a lucrative business possibility. Customers have the option of paying at the time of delivery or by monthly credit card invoicing. We will mail statements to each contract client at the end of each month, itemizing service prices and charging the service to their credit cards for payment. The company offers a new door-to-door service in Kota Masai and nearby areas that will undoubtedly pique the interest of customers. Working consumers may find this service useful and wish to test it. If they are pleased with the service, they will most likely become repeat clients. When patronage is consistent, people become devoted clients of the service. These clients will tell their friends and co-workers about Triple A & P. Triple A & P’s image will improve as more clients utilise our service, and we will gain market share. We are launching the company with a total capital of RM50,000, with contributions ranging from RM 1,500 to RM 9,000, and a loan of around RM150,000 from Bank Islam. We employ four people: the general manager, the administrative manager, the operational manager, the marketing manager, the finance manager, and the production manager. Our market target client characteristics include busy employees, busy families, students, and individuals in the neighbourhood. With our business financial situation statement, we feel we will be able to reach our business aim. We will receive our return mode in a short period of time, and our current ratio will meet our liabilities and place our firm in a comfortable stage.